2017
DOI: 10.3389/fnhum.2017.00188
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Best Times for Cognitive Functioning Using New Methods: Matching University Times to Undergraduate Chronotypes

Abstract: University days generally start at fixed times in the morning, often early morning, without regard to optimal functioning times for students with different chronotypes. Research has shown that later starting times are crucial to high school students' sleep, health, and performance. Shifting the focus to university, this study used two new approaches to determine ranges of start times that optimize cognitive functioning for undergraduates. The first is a survey-based, empirical model (SM), and the second a neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 49 publications
3
32
0
2
Order By: Relevance
“…A recent study of university students aged 18–19 found that later starting times (after 11 a.m. or 12 noon) were optimal and much later than an 8:30 a.m. start recommended for High School students of 17–18. The study also found that using a fixed time for all students would disadvantage one or more chronotypes, and evening chronotypes in particular if starts were early (Kelley et al, 2015 ; Evans et al, 2017 ). Thus, even with the benefits accrued using a 10 a.m. wake time for all students, this approach does not address the wider variation of wake times in different chronotypes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study of university students aged 18–19 found that later starting times (after 11 a.m. or 12 noon) were optimal and much later than an 8:30 a.m. start recommended for High School students of 17–18. The study also found that using a fixed time for all students would disadvantage one or more chronotypes, and evening chronotypes in particular if starts were early (Kelley et al, 2015 ; Evans et al, 2017 ). Thus, even with the benefits accrued using a 10 a.m. wake time for all students, this approach does not address the wider variation of wake times in different chronotypes.…”
Section: Discussionmentioning
confidence: 96%
“…One study in New Zealand did report improved sleep in 17 to 18-year-old students when the starting time was moved from 9:00 to 10:30 a.m., as compared to younger controls who remained at 9:00 a.m. (Borlase et al, 2013 ). A recent study of optimal times for cognitive performance for students aged 18–19 concluded that much later times were optimal, specifically after 11 a.m. or 12 noon (Evans et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation can have a negative impact on learning and memory processes, decreasing the ability to encode new memories though LTP and LTM processes, and may disrupt consolidation in sleep. Individuals have distinctive circadian patterns by chronotype that determine the best times for cognitive functions, as shown in optimum times in their 24-h profiles that identify best times (Evans et al, 2017 ). Studies of learning and memory that do not control for circadian variations may be flawed or fail to identify chronotypes as a significant factor in the variations in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, changes in light depend only on geophysical location and the pRGC/SCN timing mechanism, leading us to measure biological time as Geophysical Biological Time (GBT). GBT uses only the environmental cues of changing light in a specific geophysical location to calculate biological time and determining optimal timings for human activities (Bass and Lazar, 2016 ; Evans et al, 2017 ). The differences between GBT and UTC can be important, as shown in studies of Time Zone anomalies (Yasseri et al, 2012 ) and Daylight Savings Time (Coren, 1996 ).…”
Section: Circadian Neurosciencementioning
confidence: 99%
See 1 more Smart Citation